Daniel his Chaldie visions and his Ebrew: both translated after the originall: and expounded both, by reduction of heathen most famous stories vnto the exact proprietie of his wordes (which is the surest certaintie what he must meane:) and by ioyning all the Bible, and learned tongues to the frame of his worke. [electronic resource] (1597)
Summary goes here